As contribuições da biblioteca escolar para a promoção da leitura e da cidadania - Fiorini, Fernanda Balestrerri (2015)
This study addresses the possible contributions that the school library and reading mediation can offer to a school environment in which the habit of reading is losing its importance. Thus, this work, as well as the research on which it is based, aims to increase the use of mediation and library in the education of students who are in the final years of middle school in a municipal elementary school, located in the city of São José do Herval, as well as describe and analyze the universe of readers of the institution. This research is extremely important, since it was developed in a familiar environment to the researcher. Making use of action research method, we seek to understand the factors that influence young people whether to become readers, or whether lose interest in literary reading; but also the mediation carried out by the researcher aims to reverse the lack of interest shown by the readers so far. Therefore, this research has its theoretical basis on postulates of Michèle Petit (2008), Lucia Santaella (2004), Jorge Larrosa (2002), Judith Langer (2005) and Teresa Colomer (2007). With the application of reading practices, analysis and interpretation of data, one can see the importance of reading mediation and especially the transforming power that reading, particularly the literature, has in the lives of young students, making them able to change their way of seeing and living in the world today